(untitled) (LEARNing Landscapes, 2018)
This paper describes a mathematics task inspired by a children’s storybook, The Important Book by Margaret Wise Brown, and how secondary mathematics preservice teachers’ (PSTs’) experiences with this reform-based task influenced their development as educators. Findings suggest that PSTs enjoyed the opportunity to be creative and make connections to personal experiences. Engaging in this writing task also affected PSTs’ development as mathematics teachers as it allowed them to think more broadly about mathematics teaching and see the value in reform-based approaches for teaching.